Soft and energy drinks consumption and associated factors in Saudi adults: a national cross-sectional study - Aljaadi, Abeer M.; Turki, Abrar; Gazzaz, Arwa Z.; Al-Qahtani, Faisal Saeed; Althumiri, Nora A.; BinDhim, Nasser F. (Frontiers in Nutrition, 2023)
The consumption of soft and energy drinks poses a significant risk for non-communicable diseases, such as diabetes and heart disease. Studies in Saudi Arabia have reported elevated consumption of soft/energy drinks, but nation-wide data is not available. Therefore, this study aims to explore the prevalence of soft and energy drinks consumption and its associated factors among a representative sample of Saudi adults. The present research is a secondary data analysis of the 2021 Sharik Diet and Health National Survey (SDHNS). Current analysis used data on socio-demographics, anthropometrics, physical activity, and soft and energy drink consumption. The frequency of soft and energy drinks consumption is assessed on a weekly basis. Of the 5,194 Saudi adults, 3,928 were analyzed. Overall, 67% consumed soft drinks weekly, while 30% consumed energy drinks weekly. In multiple logistic regression, consumption of either soft drinks or energy drinks was associated with males, a younger age, lower income, and lower physical activity. Individuals with overweight or obesity were less likely to consume energy drinks [OR(95%CI): 0.73 (0.60, 0.90) and 0.83 (0.71, 0.99), respectively]. However, education level was not associated with either soft or energy drink consumption. These findings highlight the need for targeted interventions designed to reduce soft and energy drinks consumption in Saudi adults.